Effects of Maternal Micronutrient Levels and Homocysteine on Pregnancy Complications and Outcomes: A Prospective Cohort Study - Gul Ozel Dogan; Orhan Sahin (Clinical and Experimental Obstetrics & Gynecology)
Background: Metabolic processes involving homocysteine and associated micronutrients (e.g., vitamin B12 and folic acid) are critical for cellular function, vascular development, and hormonal regulation during pregnancy, and they play a crucial role in both maternal and fetal health. However, evidence on the effects of micronutrient supplementation in preventing pregnancy-related complications remains limited. This prospective cohort study aims to investigate the effects of maternal micronutrient status and homocysteine levels in early pregnancy, with a focus on their potential impact on maternal and fetal health outcomes in a Turkish population. Methods: First-trimester blood parameters and sociodemographic data were recorded from 79 pregnant women, who were then followed until delivery. Serum levels of ferritin, vitamin D, folic acid, vitamin B12, and homocysteine were measured. Maternal and fetal complications were monitored throughout pregnancy, and any pregnancy-related adverse outcomes were documented. Participants with low micronutrient levels received supplementation. Results: Pregnancy-related maternal and fetal complications were as follows: gestational diabetes mellitus (21%), gestational hypertension (13%), hypothyroidism during pregnancy (17%), and preterm birth (25%). There were no significant differences in maternal blood parameters, including vitamin B12, vitamin D, folic acid, ferritin, international normalized ratio (INR), homocysteine, or hemogram levels between pregnant women with complications and those without (p > 0.05). Conclusions: Our findings suggest that neither micronutrient levels nor homocysteine alone account for pregnancy complications. However, this study underscores the potential combined impact of these factors on maternal and fetal outcomes.